Improving the lipid oxidation in pork fat processing for Chi-aroma Baijiu through pretreatments and segmented soaking with liquor. (August 2020) - Wei, Daiyue; Li, Lingfang; He, Songgui; Yu, Jianxia; Tian, Xiaofei; Wu, Zhenqiang
Abstract: This study aimed to explore an efficient method to prepare ageing pork fat used as catalyst in the production of Chi-aroma Baijiu. Results showed that boiling after warm water treatment was the best pretreatment method, which could eliminate off-odor greatly by decreasing aldehydes, fusels, esters, alkanes, alkenes and aromatics in raw pork fat, and would significantly ( p < 0.05) improve TBARS (2-thiobarbituric acid-reactive substances) value and fatty acids dissolution during following 3-month soaking. Compared to pure alcohol solution, basic liquor mixed with fat oil as soaking solution could significantly ( p < 0.05) increase acid value. Soaking pork fat in high-alcohol-volume (500 mL ethanol/L) and then low-alcohol-volume (300 mL ethanol/L) basic liquor subsequently, could accelerate the release of fatty acids into basic liquor. Segmented soaking by adding fat oil at the 6th month following 5 months basic liquor soaking was the most efficient method, in which both TBARS value and acid value were increased, up to 2.89 ± 0.37 mg malondialdehyde (MDA)/kg and 4.97 ± 0.04 mg KOH/g, respectively, and PUFA (polyunsaturated fatty acids)/SFA (saturated fatty acids) was lowest (0.44 ± 0.00). It provides potential strategies to accelerate the ageing process of pork fat for Chi-aroma Baijiu industry. Highlights: Oxidized pork fat was used to improve liquor flavor and produce Chi-aroma Baijiu. Raw pork fat was pretreated with boiling water after warm water to eliminate off-odor. Pretreatment accelerated lipid oxidation and dissolution from pork fat in liquor soaking. The soaking liquor added fat oil could improve lipid oxidation and get higher acid value. Stage Soaking with high then low alcohol liquor further accelerated release of fatty acids.